NEW RESULTS FROM AN EXPERIMENTAL STUDY ON THE STABILISATION OF SOIL USING COIR FIBRE, FLY ASH, AND CACL2 (International Journal of Food and Nutritional Sciences, 2022)
As a result of the fact that stabilisation of soil may enhance its technical capabilities, both chemical andmechanical methods of stabilisation are now in use. In this particular research project, expansive soils are mademore stable by incorporating Coir fibre, flyash, and CaCl2.It is to your benefit to utilise coconut coir fibre toimprove soil quality since these fibres are not only inexpensive but also easily accessible in your area and kindto the environment